Antibiotic Resistance Patterns of Bacterial Isolates From Ready to Eat Jollof Rice Sold in Different Restaurant in Abakaliki and Ikwo, Ebonyi State, Nigeria - Ogba, R. C.; Nomeh, O. L.; Ekpono, C. U.; Ameh, O. A.; Awarajih, U. C.; Ibelegbu, G. E. (Journal of Science, Technology and Innovation Research, 2025)
Antibiotic resistance among foodborne pathogens poses a significant public health concern, especially in ready-to-eat foods. This study aimed to investigate the antibiotic resistance patterns of bacterial isolates from ready-to-eat jollof rice obtained from various restaurants in Abakaliki and Ikwo, Ebonyi State. A total of 10 jollof rice samples were randomly collected from various restaurants and subjected to microbiological analysis using standard methods. The susceptibility of the isolates to 12 commonly used antibiotics was assessed using the standardized Kirby Baur disc-diffusion method, and the results indicated elevated viable counts, ranging from 2.0 x 10⁴ cfu/g to 1.2 x 10⁶ cfu/g, exceeding the Centre for Disease Control's recommended limit. Coliform bacteria were detected in some samples, with counts reaching up to 4.4 x 10² cfu/g, indicating significant contamination and poor food handling practices. Eight pathogenic bacteria including Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Shigella sp, Pseudomonas aeruginosa, micrococcus sp and Bacillus sp were isolated. The antibiotic susceptibility testing revealed alarming resistance rates, particularly against Ampicillin (80%) and Erythromycin (75%), while Chloramphenicol demonstrated the highest susceptibility (85%). The findings suggest a worrying trend of antibiotic resistance linked to the misuse of antibiotics in food production. The study also underscores the urgent need for improved food safety practices, vendor training and public health awareness. Enhanced regulatory oversight and collaboration among health authorities are essential to mitigate risks associated with microbial contamination and antibiotic-resistant pathogens, ultimately safeguarding public health. Keyword: Antibiotic resistance, food safety, public health, susceptibility, foodborne pathogens.